A Secure Approach Out-of-Band for e-Bank with Visual Two-Factor Authorization Protocol - Laerte Peotta de Melo; Dino Macedo Amaral; Robson de Oliveira Albuquerque; Rafael Timóteo de Sousa Júnior; Ana Lucila Sandoval Orozco; Luis Javier García Villalba (Cryptography)
The article presents an innovative approach for secure authentication in internet banking transactions, utilizing an Out-of-Band visual two-factor authorization protocol. With the increasing rise of cyber attacks and fraud, new security models are needed that ensure the integrity, authenticity, and confidentiality of financial transactions. The identified gap lies in the inability of traditional authentication methods, such as TANs and tokens, to provide security in untrusted terminals. The proposed solution is the Dynamic Authorization Protocol (DAP), which uses mobile devices to validate transactions through visual codes, such as QR codes. Each transaction is assigned a unique associated code, and the challenge must be responded to within 120 s. The customer initiates the transaction on a computer and independently validates it on their mobile device using an out-of-band channel to prevent attacks such as phishing and man-in-the-middle. The methodology involves implementing a prototype in Java ME for Android devices and a Java application server, creating a practical, low-computational-cost system, accessible for use across different operating systems and devices. The protocol was tested in real-world scenarios, focusing on ensuring transaction integrity and authenticity. The results show a successful implementation at Banco do Brasil, with 3.6 million active users, demonstrating the efficiency of the model over 12 years of use without significant vulnerabilities. The DAP protocol provides a robust and effective solution for securing banking transactions and can be extended to other authentication environments, such as payment terminals and point of sale devices.